Doxorubicin Exposure Affects Oocyte Meiotic Maturation through DNA Damage-Induced Meiotic Arrest. (31st July 2019) - Ding, Zhi-Ming; Zhang, Shou-Xin; Jiao, Xiao-Fei; Hua, Li-Ping; Ahmad, Muhammad Jamil; Wu, Di; Chen, Fan; Wang, Yong-Shang; Zhang, Xi-Yu; Meng, Fei; Duan, Ze-Qun; Miao, Yi-Liang; et al.
Abstract: Developments in chemotherapeutics have enhanced the survival rate of cancer patients, however, adverse effects of chemotherapeutics on ovarian functions causes the fertility loss in young female cancer patients. Doxorubicin (DOX), as an anthracycline antitumor antibiotic, is extensively used to cure various malignancies. Recent studies have suggested that DOX can cause ovarian damage and affect the oocyte maturation, nevertheless the mechanism by which DOX on oocytes meiosis is poorly understood. In this study, we explored the mechanism for DOX-induced oocytes meiotic failure in vitro at human relevant exposure levels and time periods. Results described that DOX (100 nM) can interrupt the mouse oocytes meiotic maturation directly with reduced first polar body extrusion. Cell cycle analysis showed that most oocytes were arrested at metaphase I (MI) stage. However, DOX treatment had no effect on spindle structure but chromosomal misalignment. We observed that kinetochore-microtubule structure was affected and the spindle assemble checkpoint was provoked after DOX treatment. Moreover, severe DNA damage was found in DOX-treated oocytes indicated by the positive γ-H2A.X foci signal, which then may trigger oocytes early apoptosis. Besides, metaphase II oocytes with disorganized spindle morphologies and misaligned chromosomes were observed after DOX treatment. In conclusion, DOX have the potential to disrupt oocyte meiotic maturation through DNA damage induced meiotic arrest mediated by spindle assemble checkpoint activation. These findings can contribute to design the new therapies to alleviate DNA damage to preserve fertility for young female cancer patients with chemotherapeutics.